The mythology class where Philippine legends become reality: a graphic novel - Arre, Arnold (Tuttle Publishing, 2022)
"This entertaining graphic novel fuses Philippine myth and magic with contemporary action. Summoned to a secret meeting by the mysterious Madame Enkanta, Nicole finds herself face to face with living creatures from Philippine mythology and folkore that she never imagined existed in real-life. Tikblangs, kapres and a range of engkantos-fantasy figures from her grandfather's bedtime stories-challenge her previously-held notions of reality! With her newfound friends, University of the Philipping anthropology student Nicole Lacson embarks on a quest into a realm of myth and magic, where she fights alongside the heroes of her childhood against an ancient evil. Navigating the streets of metro Manila, a ragtag crew of college students takes an unexpected turn into a fascinating realm of daring deeds and dark menace. What starts as fieldwork for these students desperate to finish their theses takes on larger and more sinister implications. Historical and mythological Filipino heroes like Sulayman, Kubin and Lam-ang make guest appearances. With these ancient personas behind him, together the class must face down and repel an invasion of chaotic forces, recapturing the enkantos who have escaped and are unleashing mischief and evil in the human world. Borrowing elements from The Lord of the Rings and The Phantom Tollbooth, author and creator Arnold Arre reinvents age-old Filipino fables, constructing a rich world of folklore fantasy for a new generation. This is world-building of the highest order, balancing the scope and magnitude of an adventure epic with the humor, warmth and insight of a classic coming-of-age tale"--